2015
DOI: 10.1371/journal.pone.0138867
|View full text |Cite
|
Sign up to set email alerts
|

The Y-Box Binding Protein 1 Suppresses Alzheimer’s Disease Progression in Two Animal Models

Abstract: The Y-box binding protein 1 (YB-1) is a member of the family of DNA- and RNA binding proteins. It is involved in a wide variety of DNA/RNA-dependent events including cell proliferation and differentiation, stress response, and malignant cell transformation. Previously, YB-1 was detected in neurons of the neocortex and hippocampus, but its precise role in the brain remains undefined. Here we show that subchronic intranasal injections of recombinant YB-1, as well as its fragment YB-11−219, suppress impairment of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 38 publications
0
16
0
Order By: Relevance
“…Existing drugs may have certain toxic side effects on cells, and thus, their biocompatibility, biosafety and biodegradability are poor. Moreover, neural stem cells are characterized by low survival rate, slow proliferation, and slow differentiation and maturity . Promoting nerve regeneration through small molecule compounds may be a new therapeutic strategy.…”
Section: Discussionmentioning
confidence: 99%
“…Existing drugs may have certain toxic side effects on cells, and thus, their biocompatibility, biosafety and biodegradability are poor. Moreover, neural stem cells are characterized by low survival rate, slow proliferation, and slow differentiation and maturity . Promoting nerve regeneration through small molecule compounds may be a new therapeutic strategy.…”
Section: Discussionmentioning
confidence: 99%
“…First, Y-box-binding protein 1 (YB-1), a highly conserved cold shock domain family protein, regulates G3BP1 via binding to its 5'UTR to activate its translation (Somasekharan et al, 2015). YB-1 has also been linked to neurodegeneration such that YB-1 expression is neuroprotective in a mouse model of sporadic AD (Bobkova et al, 2015). Specifically, intranasal administration of YB-1 into mice induced the formation of YB-1 granules and positively correlated with a reduction in β-amyloid plaques and showed an improvement in short-term working memory (Bobkova et al, 2015).…”
Section: Regulation Of G3b P1 Mrnamentioning
confidence: 99%
“…The authors noted that intact exogenous YB-1 was detectable within cells for at least 2 hours, suggesting that it may be involved in other mechanisms regulating cell survival in conditions of AD-type neurodegeneration (Bobkova et al, 2015).…”
Section: Regulation Of G3b P1 Mrnamentioning
confidence: 99%
See 1 more Smart Citation
“…CK1ε also functions as a major regulator of circadian rhythms 60 , leading speculation that these disturbances to CK1ε expression in AD could be related to the sleep disturbances experienced by patients. Previous in vivo experiments have shown that treatment of 5xFAD mice with recombinant nuclease-sensitive element-binding protein 1 (YBOX 1) results in decreased levels of Aβ in the brain, but also inhibits the fibrillization of Aβ 1-42 in vitro 61 . We show that oAβ exposure caused a decrease in phosphorylated YBOX 1 in the exposed neurons (fold change 0.3, p = 0.054).…”
Section: Identified Proteinsmentioning
confidence: 99%